Investigation on thermal barrier coating and thermal behaviour at high temperature - Ding, Siwen (2017)
The oxidation behaviour of diffusion and overlay coating, manufactured by pack cementation and high velocity oxygen fuel (HVOF) techniques, was studied under isothermal condition at a temperature of 1100 °C for up to 500 hours. Detailed analysis on oxide thickness coupled with cross section microstructure observation was carried out. The results shown sub-parabolic oxide growth for all samples. To simulate a real operating condition for the thermal barrier coating (TBC) system, high temperature oxy-acetylene flame based burner rig was designed, manufactured and calibrated. A maximum surface temperature of 1400 °C detected by a single wavelength pyrometer with a 700 °C through sample thickness thermal gradient was achieved. A TBC system in which the ceramic top layer deposited by air plasma spray (APS) technique was tested under such condition. Several damage/failure types were identified in comparison with samples tested under isothermal loading. A novel physical based mathematical moving boundary problem model utilizing asymptotic analysis that predicts the growth of the oxide layer on a binary bond coat system was proposed. The governing equations were discretized and solved numerically using finite difference and Newton’s iteration method respectively. Numerical results obtained from this model had shown a good qualitative agreement from comparison with the experimental studies.